Functional inactivation of dorsal hippocampus impairs active place avoidance in rats - Cimadevilla, J M; Fenton, A A; Bures, J (Neuroscience letters, 2000)
This paper assesses the contribution of hippocampus to the spatial orientation of Long-Evans rats in a new place avoidance task. The animals learn to avoid a mild footshock in a segment of a rotating arena. Since the punished region is defined in the coordinate system of the stationary room the subject is forced to move away from the prohibited segment even if it is immobile. After bilateral injection of tetrodotoxin (5 ng in 1 microl of saline) into the dorsal hippocampus rats were not able to avoid the punished place while a similar injection of saline did not affect performance. The results suggest the task is suitable for assessing the hippocampus-dependent spatial abilities of laboratory rodents.
Keywords: Rats, Long-Evans; krysa rodu Rattus; Animals; Avoidance Learning; Catheter Ablation; Hippocampus; orientace; hipokampus; mužské pohlaví; zvířata; potkani Long-Evans; Male; Tetrodotoxin; katetrizační ablace; učení vyhýbat se; Rats; Orientation; tetrodotoxin